At the Edge of Coexistence: Borders, Power, and Ecology in Sri Lanka’s Human–Elephant Conflict - Sandunlekha, E.; Rajni, G.; Dassanayake, H.B. (university of jaffna, 2025)
In Sri Lanka, the ‘human-elephant conflict’ (HEC) results hundreds of deaths for both humans and elephants each year. Policy discourse on solutions is shaped by three stakeholder perspectives, mainly from the government’s developmentalist agenda, local citizens who experience the conflict, and the conservationists. The narratives on solutions are framed by dominant stakeholder perspectives, often presented and highly technocratic, promoting strategies focused on anthropocentric and technology-facilitated ‘controlling’ wildlife via electric fences, translocation, isolation, or offering incentives and compensation for humans to ‘tolerate’ elephants. In this paper we argue that dominant approaches on the HEC in Sri Lanka neglect the broader political-economic structures that shape human-elephant relationships, including historical patterns of land use, development, and governance. Given that elephants roam over half of the geographical areas of the country, anthropocentric approaches attempt to create borders to elephant habitat. This research outlines the decline of elephants in three distinct phases, and the border creation narratives that developed along these phases. The paper analyses government and policy narratives on elephants from a genre approach, mapping the rhetorical approach used by policy makers (National Act Plan, 2020). For this purpose, this study analyses government reports, policy outlines, development plans and administrative reports to understand how such border creation was framed, thereby also eliciting other forms of borders such as ethno-religious, wildlife, or rural-urban borders, creating a hierarchy of agents of border creation defined by relative power, mostly created through ‘othering’ narratives, from humans vs wildlife, majoritarian vs minority, modern - ‘unsophisticated’, etc. The first phase of decline in elephant population occurred in the early part of the third quarter of the 19th century. Between 1853 and 1872, around 2,500 elephants were exported during a time when elephants were domesticated and traded internationally (Gunawansa et al., 2023). The second phase spanned from the 1870s to the 1940s, when the expansion of the plantation sector played a major role in reducing elephant numbers. The third and ongoing phase began in the post-independence era. This period saw a rise in development centering Sri Lanka’s dry zone. One of the largest initiatives, the Accelerated Mahaweli Development Program, aimed to convert 260,000 hectares into agricultural land through extensive irrigation. This transformation led to major changes in land use, resulting in the destruction of elephant habitats and a rise in the HEC. Likewise, more recent developmental projects such as the Mattala airport in the southern Hambantota district were established by clearing forest covers of approximately 2000 ha, causing a fragmentation of wild elephant habitats and impeding elephant corridors (Gunawansa et al., 2023). Borders are more than spatial markers, and socio-cultural and political constructs shaped by power, development, and identity. In Sri Lanka, the technocratic framing of human-elephant conflict policies reflects a broader developmentalist agenda that echoes colonial and postcolonial attempts to impose order and control over space and nature. The creation of physical borders through electric fences, translocation, and land conversion parallels historical global patterns where modernization and state-building have often entailed the marginalization of indigenous ecologies and non-human actors. Among the drivers of this border creation and maintenance process is the narrative of how agriculture is an economic and cultural cornerstone of the nation. A clear sign of how agricultural modernization denies cohabitation of all species is how Sri Lanka’s dry zone indicates that shifts in agricultural practices are closely linked to the rising frequency of crop raiding by elephants (Köpke et al., 2021). Traditional land-use methods like chena cultivation, which included long fallow periods, once supported more coexistence among humans and elephants. These fallow lands provided elephants with seasonal food sources, reducing their need to raid active crops. Furthermore, traditional crops grown in chena fields were typically outside the dietary preferences of elephants, discouraging them from approaching human settlements during cultivation periods. However, the move towards permanent agriculture and cash crops, driven by economic incentives, has altered cropping patterns to align more closely with what elephants consume. Inevitably, elephants are increasingly drawn to cultivated areas. The common framing of Sri Lanka as an agricultural country, in the past and into the future, tends to obscure the deeper historical and structural dimensions of the conflict. This tunnel-eyed view limits how we perceive elephants: not as beings with agency, but as subjects to be managed within human-dominated systems. Compounding this issue is climate change. Through droughts, crop failures, and shifting vegetation patterns, both humans and elephants are increasingly forced to compete over scarce resources. However, climate and development policies often exclude the voices of rural and marginalized communities, particularly women, leading to decisions that benefit elites while displacing both wildlife and vulnerable populations. This paper employs a political ecology-centric perspective which at its core prioritizes a dialectic between nature and society. It examines how the construction of borders over the human-elephant conflict are deeply rooted in political and economic power structures rather than being merely the result of overpopulation or technology deficiencies, as many mainstream narratives suggest. This approach delves into issues such as land degradation and resource scarcity, often revealing them as consequences of capitalist development, state interventions, and unequal access to land and natural resources. Consequently, the human-elephant conflict can be understood as the outcome of historical land dispossession, the appropriation of natural spaces, agricultural expansion, conservation practices, and hyper-consumerism that prioritizes economic growth over the needs of local ecosystems.
Keywords: Human-elephant conflict; Borders; Political ecology; Climate change; Development